SISTEM PENDUKUNG KEPUTUSAN MOISTURIZER LIDAH BUAYA UNTUK KULIT BERMINYAK MENGGUNAKAN METODE SAW BERBASIS WEBSITE - Maulidiyah, Nisful Lailiyatul (Universitas Multi Data Palembang, 2025)
Public awareness of proper skincare, especially for oily skin in tropical climates, has been steadily increasing. Aloe vera is widely recommended due to its lightweight texture and soothing properties. However, product selection often remains subjective. This study develops a web-based Decision Support System (DSS) utilizing the Simple Additive Weighting (SAW) method to assist consumers in choosing suitable aloe vera–based moisturizers for oily skin. The system was built using the Waterfall development model, covering requirement analysis, UML-based system design, implementation, and black box testing. Four evaluation criteria were applied: skin compatibility, price, additional ingredients, and texture. Among the ten assessed products, “Tératu Beauty – Aloe Vera Soothing Gel” achieved the highest preference score of 0.875, while “The Body Shop – Aloe Soothing Day Cream” ranked lowest with a score of 0.425. The results demonstrate that the SAW-based DSS can provide accurate and efficient product recommendations, offering potential contributions to the growth of natural ingredient–based skincare industries.